Micro- and Nano-Air Vehicles: State of the Art - Luca Petricca; Per Ohlckers; Christopher Grinde (International Journal of Aerospace Engineering)
Micro- and nano air vehicles are defined as “extremely small and ultra-lightweight air vehicle systems” with a maximum wingspan length of 15 cm and a weight less than 20 grams. Here, we provide a review of the current state of the art and identify the challenges of design and fabrication. Different configurations are evaluated, such as fixed wings, rotary wings, and flapping wings. The main advantages and drawbacks for each typology are identified and discussed. Special attention is given to rotary-wing vehicles (helicopter concept); including a review of their main structures, such as the airframe, energy storage, controls, and communications systems. In addition, a review of relevant sensors is also included. Examples of existing and future systems are also included. Micro- and nano-vehicles with rotary wings and rechargeable batteries are dominating. The flight times of current systems are typically around 1 hour or less due to the limited energy storage capabilities of the used rechargeable batteries. Fuel cells and ultra capacitors are promising alternative energy supply technologies for the future. Technology improvements, mainly based on micro- and nanotechnologies, are expected to continue in an evolutionary way to improve the capabilities of future micro- and nano air vehicles, giving improved flight times and payload capabilities.